Support as a strategy for COSEMS RJ to strengthen sus municipal management in the State of Rio de Janeiro (Research, Society and Development, 2021)
We present an account of the experience of the Support strategy at COSEMS RJ. This article provides a systematization of the reflections on the responsibilities and functions of the supporter who develops such a strategy. Since 2012, COSEMS RJ has built a model that offers technical support to municipal management, offering regionalized support, mainly from SUS governance spaces. The reflection about the supporter's work was activated through Permanent Education (EP) practices. The activities that configure the work of this strategy in COSEMS RJ were organized from the verb (acronym) support, unfolding in other verbs: Support; Participate; Guide; Encourage; Articulate and reflect. The systematization of the roles of supporters, with greater clarity for them in relation to their roles. In addition, it favored the visibility of the work with municipal managers and technical teams.